Is transoral robotic surgery a safe and effective multilevel treatment for obstructive sleep apnoea in obese patients following failure of conventional treatment(s)?. (July 2017) - Garas, George; Kythreotou, Anthousa; Georgalas, Christos; Arora, Asit; Kotecha, Bhik; Holsinger, Floyd C.; Grant, David G.; Tolley, Neil
Abstract: A best evidence topic was written according to a structured protocol. The question addressed was whether TransOral Robotic Surgery (TORS) is a safe and effective multilevel treatment for Obstructive Sleep Apnoea (OSA) in obese patients following failure of conventional treatment(s). A total of 39 papers were identified using the reported searches of which 5 represented the best evidence to answer the clinical question. The authors, date, journal, study type, population, main outcome measures and results are tabulated. Existing treatments for OSA - primarily CPAP - though highly effective are poorly tolerated resulting in an adherence often lower than 50%. As such, surgery is regaining momentum, especially in those patients failing non-surgical treatment (CPAP or oral appliances). TORS represents the latest addition to the armamentarium of Otorhinolaryngologists - Head and Neck Surgeons for the management of OSA. The superior visualisation and ergonomics render TORS ideal for the multilevel treatment of OSA. However, not all patients are suitable candidates for TORS and its suitability is questionable in obese patients. In view of the global obesity pandemic, this is an important question that requires addressing promptly. Despite the drop in success rates with increasing BMI, the success rate of TORS in non-morbidly obese patients (BMI = 30-35kgm -2 ) exceeds 50%. A 50% success rate may at first seem low, but it is important to realize that this is a patient cohort suffering from a life-threatening disease and no option left other than a tracheostomy. As such, TORS represents an important treatment in non-morbidly obese OSA patients following failure of conventional treatment(s). Highlights: There is a paucity of evidence on the subject with complete absence of RCTs. The literature supports TORS as a safe multilevel treatment for OSA. The effectiveness of TORS for OSA drops with increasing BMI. TORS represents an important treatment for OSA in non-morbidly obese patients after failure of conventional treatment(s). There is no role for TORS as an OSA treatment in morbidly obese patients.